An investigation into maternal use of telegraphic input to children with Down syndrome. Issue 1 (7th January 2020) - LORANG, Emily; VENKER, Courtney E.; STERLING, Audra
Abstract: Maternal input influences language development in children with Down syndrome (DS) and typical development (TD). Telegraphic input, or simplified input violating English grammatical rules, is controversial in speech–language pathology, yet no research to date has investigated whether mothers of children with DS use telegraphic input. This study investigated the quality of linguistic input to children with DS compared to age-matched children with TD, and the relationship between maternal input and child language abilities. Mothers of children with DS simplified their input in multiple ways, by using a lower lexical diversity, shorter utterances, and more telegraphic input compared to mothers of children with TD. Telegraphic input was not significantly correlated with other aspects of maternal input or child language abilities. Since children with DS demonstrate specific deficits in grammatical compared to lexical abilities, future work should investigate the long-term influence of maternal telegraphic input on language development in children with DS.